Difficulties encauntered In visual arts given in high- school education in Turkey and solution proposals - Kavuran, Tamer; Dede, Bayram (My University, 2014)
In today’s societies prudential Education Visual Arts has a gradually improving priority and importance. In Turkey from declaring of Republic until now, Visual Arts Coming with perpetual changing, confront us as the lesson of which aim hasn’t become clear. Even nowadays, uncertainty of aims of art training in high schools helps us to understand the hardship of the Issue, ıs Visual Arts a free time activity that put in the high School Corricula. Or an activity that has many acquisitions in which it harbours its aims. What’s the actual aim of Visual Arts? These questions have unfortunately been unanswered. This question’s answer is; most or people from the ones who prepare the Visual Arts Training Curricula to the teachers who teach the lesson don’t actually know the functions and aim of Visual Arts Because of this and because of not being understood by students’ parents and directors the Visual Arts lesson hasn’t reached its aim. Besides, the students squeezed among the scholarship exams, level setting exams, school and courses, slide over or make up excuses that it is a talent. In any case in schools that have many problems, visual arts have become a big matter’s skein that come from the past and can’t be solved.
Bildiri - Yayımlanmış
4TH WORLD CONFERENCE ON LEARNING, TEACHING AND EDUCATIONAL LEADERSHIP (WCLTA-2013) 27-29 October 2013 University of Barcelona, Barcelona – Spain
Keywords: Education; Art; Visual Arts Education;